Experimental investigation of the constant and time-dependent dynamic diffusion coefficient: Implication for CO2 injection method. (1st May 2020) - Liu, Zhengdong; Cheng, Yuanping; Wang, Liang; Pang, Bin; Li, Wei; Jiang, Jingyu
Highlights: A new diffusion model considering loss amount is proposed. Constant and time-dependent diffusion coefficient are compared and diffusion distance are analyzed. A new stepwise pressure-raising injection method of CO2 injection method is discussed. Abstract: Gas diffusion in coal is an important transport mechanism that plays a crucial role in carbon dioxide (CO2 ) storage in and methane (CH4 ) extraction from coal seams. Studies on coal diffusion are largely based on experimental work on different coal particles and the establishment of uni-pore or bidisphere theoretical models. However, problems remain in both experimental and theoretical analyses. Therefore, the initial desorption time of adsorbed gas, something that is not done using conventional experimental devices, was revealed in this study. The initial desorption time was obtained by calculating the relationship between the amount of gas collected and the theoretical amount of free gas. An improved diffusion model considering lost gas was established based on the initial desorption time of adsorbed gas. The mpdel provides diffusion coefficients for different equilibrium pressures and particle sizes on the basis of a unipore diffusion model. By correlating diffusion coefficient and time, an empirical time-dependent diffusion model was established to solve the dynamic diffusion coefficient under different conditions. Finally, in order to substantiate that the variation in diffusion length is the primary cause of the variation of diffusion coefficients with time, the variation of diffusion length with desorption time was obtained. As a result, a stepwise pressure-rasing method was proposed. This new injection method can effectively improve CO2 storage and CH4 recovery from coal seams. The study has a certain guiding significance in engineering practice.